Constrained liners revisited: favourable mid-term results in patients with high-risk of dislocation: technical considerations for the optimal outcome. Issue 1 (January 2023) - Kenanidis, Eustathios; Kakoulidis, Panagiotis; Anagnostis, Panagiotis; Potoupnis, Michael; Tsiridis, Eleftherios
Background: The outcomes of constrained liners (CLs) in total hip arthroplasty (THA) remain inconclusive. We evaluated the mid-term performance of CLs in a consecutive series of high-risk dislocation patients undergoing primary or revision THA performed by a single surgeon. The survival, dislocation rate, complications, and functional patients' scores were assessed. Surgical tips to enhance outcomes were reviewed. Methods: 45 patients who received the Trident Tripolar CL between 2010 to 2019 were retrospectively evaluated from Arthroplasty Registry Thessaloniki. There were 17 primary and 28 revision THAs. The primary indications for using CL were severe abductor insufficiency or comorbidities, increasing the dislocation risk in primary, and recurrent dislocation or abductor insufficiency in revision THAs. The mean patient's age was 68.5 (±14.5) years, and the mean follow-up 3.81 (±1.66) years. Results: There were 2 dislocations and 1 deep infection in the revision group. For any reason, the cumulative 6-year survival rate was 93.3%, 100% for primary, and 89.3% for revision THAs. The mean overall CL survival was 76.3 months for any reason (95% CI, 68.1–84.5) and 80.5 months for dislocation (95% CI, 75.8–85.2). The mean postoperative functional scores were significantly improved ( p  < 0.001) at the latest follow-up. Conclusions: CLs can provide hip stability and durable fixation in selected low-demand patients with high-risk for dislocation after primary and revision THA at mid-term follow-up. Careful patient selection and the refined surgical technique aiming at the neutral liner position and considering the high CLs' offset relative to stem-neck impingement are necessary to maximise outcomes.